PestDisPlace transforms pest and disease monitoring with collaborative (or community) surveillance and genomic analysis - Cuellar, Wilmer; Rodriguez, Rafael (2025)
.The Alliance of Bioversity International and CIAT-developed platform, PestDisPlace, is transforming pest and disease monitoring by providing real-time community tracking and genomic analysis, enabling rapid-response strategies in the Global South. PestDisPlace has helped successfully track Cassava Witches’ Broom Disease (CWBD) outbreaks in Brazil and French Guiana and is currently used in Ecuador to for preemtive monitoring and early warning of Fusarium TR4. These devastating diseases pose high phytosanitary risks and exacerbate food insecurity. PestDisPlace has informed policy, improved early warning systems, and contributed to climate-driven pest research, and agricultural workers’ capacities, which are being applied for more effective disease management.